Differential Functionality of Right and Left Parietal Activity in Controlling a Motor Vehicle - Brooks, Justin R.; Garcia, Javier O.; Kerick, Scott E.; Vettel, Jean M. (Frontiers in Systems Neuroscience, 2016)
Driving a motor vehicle is an inherently complex task that requires robust control to avoid catastrophic accidents. Drivers must maintain their vehicle in the middle of the travel lane to avoid high speed collisions with other traffic. Interestingly, while a vehicle’s lane deviation is critical, studies have demonstrated that heading error is one of the primary variables drivers use to determine a steering response, which directly controls the position of the vehicle in the lane. In this study, we examined how the brain represents the dichotomy between control/response parameters (heading, reaction time, and steering wheel corrections) and task-critical parameters (lane deviation). Specifically, we examined EEG alpha band power (8Hz – 13Hz) from estimated sources in right and left parietal regions, and related this activity to four metrics of driving performance. Our results demonstrate differential task involvement between the two hemispheres: right parietal activity was most closely related to lane deviation, whereas left parietal activity was most closely related to heading error, reaction time, and steering responses. Furthermore, heading error, reaction time, and steering wheel corrections increased over the duration of the experiment while lane deviation did not. Collectively, our results suggest that the brain uses differential monitoring and control strategies in the right and left parietal regions to control a motor vehicle. Our results suggest that the regulation of this control changes over time while maintaining critical task performance. These results are interpreted in two complementary theoretical frameworks: the uncontrolled manifold and compensatory control theories. The central tenet of these frameworks permits performance variability in parameters (i.e., heading error, reaction time, and steering) so far as it does not interfere with critical task execution (i.e., lane deviation). Our results extend the existing research by demonstrating potential neural substrates for this phenomenon which may serve as potential targets for brain-computer interfaces that predict poor driving performance.